ANALYSIS OF THE EFFECT OF SUKUK IJARAH ISSUANCE ON THE PROFITABILITY OF COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2018-2021 PERIOD - Fathia Hidayat; Zuwardi Zuwardi (Jurnal Ekonomi dan Bisnis, 2023)
This thesis is entitled "Analysis of the Effect of Issuing Sukuk Ijarah on the Profitability of Companies Listed on the Indonesia Stock Exchange for the 2018-2021 Period" which was compiled by Fathia Hidayat with NIM 3419154 Sharia Accounting Study Program, Faculty of Islamic Economics and Business, State Islamic University (UIN) Sjech M. Djamil Djambek Bukittinggi with guidance from Mr. Zuwardi., MA. The background of this research is the issuance of sharia bonds (sukuk) with Ijarah contracts by several publicly listed companies listed on the Indonesia Stock Exchange with the aim of strengthening capital in order to support business development activities in the form of financing distribution which fluctuates (increases and decreases). This type of research is quantitative research. The data used is secondary data. Data collection techniques using the documentation method. Selection of the sample in this study using purposive sampling. The number of samples obtained is 36 samples. Methods of data analysis are descriptive statistics, simple linear regression, classical assumption test, and hypothesis testing. The results show that the variable issuance of Islamic bonds (sukuk) with Ijarah contracts is negatively correlated and has no significant effect on Profitability (ROA) in all of these companies. This is indicated by the probability results showing sig 0.259 > 0.05 or the t test -1.149 <t table 2.032 so that H1 is rejected. And the R square value in this study shows that Sukuk Ijarah contributes weakly to ROA profitability, namely 3.7%, the remaining 96.3% is explained by other variables.